An e-portfolio acceptance model from lecturers perspective in Taif University - Alzahrani, Mohammed Ali R. (2015)
E-portfolio has received a great deal of attention in the past ten years. E-portfolio is an effective tool for teaching and learning involving students and lecturers supported by the faculty’s feedback. In line with this attention, the integrated components making connections between students and lecturers result further improvement on academic E-portfolio perspective. Lecturers’ performance has the capability of being evaluated and monitored across multi disciplines. However, in higher education a number of issues may arise with the usage of E-portfolio such as the resistance of technology acceptance and adoption. The main objective of this research is to investigate the lecturers’ E-portfolio acceptance in higher education. An E-portfolio acceptance model was proposed which adopts a combination of Technology Acceptance Model (TAM) and Diffusion of Innovation Theory (DoI). The reliability and validity of data analysis were established through experts’ validation and RASCH Model while the research hypotheses were tested using the Structural Equation Modeling (SEM). The research involved a preliminary data collection as a first survey and finally followed by the final data collection to verify the reliability and validity of the instruments and proposed model. The latter survey was conducted using questionnaires and interviews where samples were collected from 286 lecturers working in 12 faculties in a newly established public university namely the Taif University in Saudi Arabia as a case study. Interviews were held to explain further on the quantitative findings. The findings suggest that by combining the TAM with the DoI is significant to assess the lecturers’ acceptance of E-portfolio system in higher education. Further result revealed that there is a positive effect on E-portfolio acceptance factors in terms of actual use and intention to use through the system usefulness, easy to use, observability and trialability.